2015
DOI: 10.1530/rep-14-0412
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen promotes luteolysis by redistributing prostaglandin F2α receptors within primate luteal cells

Abstract: Prostaglandin F2α (PGF2α) has been proposed as a functional luteolysin in primates. However, administration of PGF2α or prostaglandin synthesis inhibitors in vivo both initiate luteolysis. These contradictory findings may reflect changes in PGF2α receptors (PTGFR) or responsiveness to PGF2α at a critical point during the life span of the corpus luteum. The current study addressed this question using ovarian cells and tissues from female cynomolgus monkeys and luteinizing granulosa cells from healthy women unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 85 publications
0
11
0
Order By: Relevance
“…PGF2α increases THBS1 and THBS2 mRNAs in the bovine corpus luteum, where THBS1 plays a role in luteal regression (5). PGF2α receptors present in granulosa cells of the primate ovulatory follicle and young corpus luteum are not capable of signal transduction (26), so the PGF2α pathway is not available to regulate expression of thrombospondins, despite elevated follicular PGF2α levels. PGF2α receptors in primate luteal cells can mediate PGF2α signals later in the luteal phase (26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PGF2α increases THBS1 and THBS2 mRNAs in the bovine corpus luteum, where THBS1 plays a role in luteal regression (5). PGF2α receptors present in granulosa cells of the primate ovulatory follicle and young corpus luteum are not capable of signal transduction (26), so the PGF2α pathway is not available to regulate expression of thrombospondins, despite elevated follicular PGF2α levels. PGF2α receptors in primate luteal cells can mediate PGF2α signals later in the luteal phase (26).…”
Section: Discussionmentioning
confidence: 99%
“…PGF2α receptors present in granulosa cells of the primate ovulatory follicle and young corpus luteum are not capable of signal transduction (26), so the PGF2α pathway is not available to regulate expression of thrombospondins, despite elevated follicular PGF2α levels. PGF2α receptors in primate luteal cells can mediate PGF2α signals later in the luteal phase (26). While prostaglandins are not a key regulators of thrombospondin protein levels in the primate ovulatory follicle, prostaglandins may regulate thrombospondin expression and activity in the primate corpus luteum, especially during luteal regression.…”
Section: Discussionmentioning
confidence: 99%
“…Prostaglandin (PG) F 2a is a bioactive lipid metabolite of arachidonic acid produced through the sequential reaction of cyclooxygenases and PGF synthase. PGF 2a exerts a wild range of pathological and physiological functions, including reproduction (8), blood pressure (9), and bone remodeling (10), by binding to its receptor (F-prostanoid [FP]). Experimental and clinical studies showed that PGF 2a is involved in different inflammatory conditions, including rheumatic diseases, asthma, atherosclerosis, ischemia-reperfusion, septic shock, and obesity (11).…”
mentioning
confidence: 99%
“…Based on this result, the administration of oxytocin and PGF2α hormones can increase the birth process stimulation in coral platy fish broodstock, although the best performance was obtained from the administration of PGF2α hormone as increased by 169% compared to control. The PGF2α hormone is often used in animals based on the principle of the hormone administration which can lyse or degrade the corpus luteum followed by decreased progesterone secretion that causes reproductive cycle alteration (Kim et al, 2015;Plewes et al, 2020).…”
Section: Discussionmentioning
confidence: 99%